ANALISIS POTENSI PETERNAK DALAM PENGEMBANGAN SAPI BALI DI KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Pieter M. Ririmasse (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
Natural resources, sustainable animal feed resources, and human resources are factors that need to be considered in carrying out the development of beef cattle such as Bali cattle. As an economy-oriented production activity, the performance of livestock business with a regional approach is largely determined by the role of breeders as the main factors, both individually and as a group. This study aims were both to know and determine the potential of individual breeders in Bali cattle development in Taniwel District. In the study, three sample villages were selected using purposive sampling method, while the total respondents selected were 30 breeders who were determined by purposive sampling. The variables observed were the basic potential of the breeders which included breeding experience, education (formal and non-formal, literacy skills), communication intensity, the potential of the breeder workforce, the potential for farmer technology mastery, and the potential for providing input to breeders' production. The data were collected then tabulated and analyzed using the average value and standard deviation. The results showed that the basic potential score of breeders was 94.16, the score for the workforce potential of the breeders was 6.17 in the low category, the potential mastery of technology owned by the breeders was in the low category with a score of 4.23, and the score The potential for providing input by breeders is 16 in the low category. It can be concluded that the final score of potential breeders in developing Bali cattle in Taniwel District is in the low category with a score of 409.39.